Systems chemical analytics: introduction to the challenges of chemical complexity analysis. (18th July 2019) - Schmitt-Kopplin, Philippe; Hemmler, Daniel; Moritz, Franco; Gougeon, Régis D.; Lucio, Marianna; Meringer, Markus; Müller, Constanze; Harir, Mourad; Hertkorn, Norbert
Abstract : We present concepts of complexity, and complex chemistry in systems subjected to biotic and abiotic transformations, and introduce analytical possibilities to disentangle chemical complexity into its elementary parts as a global integrated approach termed systems chemical analytics . Abstract : Understanding complex (bio/geo)systems is a pivotal challenge in modern sciences that fuels a constant development of modern analytical technology, finding innovative solutions to resolve and analyse. In this introductory paper to the Faraday Discussion " Challenges in the analysis of complex natural systems ", we aim to present concepts of complexity, and complex chemistry in systems subjected to biotic and abiotic transformations, and introduce the analytical possibilities to disentangle chemical complexity into its elementary parts ( i.e. compositional and structural resolution) as a global integrated approach termed systems chemical analytics .